The role of top managers in implementing corporate sustainability: A systematic literature review on small and medium-sized enterprises - Jannika Kutzschbach; Parvina Tanikulova; Rainer Lueg (Administrative Sciences, 2021)
This systematic literature review investigates whether corporate sustainability (CS), according to the triple bottom line concept (TBL), is implemented in small and medium-sized enterprises (SMEs) and further identifies associated drivers. Building on upper echelon theory (UET) and the Schwartz value system (SVS) this study aims to analyze and contextualize extant empirical research. We developed a PRISMA-based framework to select relevant studies systematically. Based on an initial sample of 1249 articles between 2000 and 2020, we provide critical analysis of 31 best practice, peer-reviewed journal articles. Our findings suggest seven specifications of CS in SMEs that are driven by either internal or external motivations. Our review reveals that, overwhelmingly, SMEs engage in CS but fail to report it ("green blushing"). Furthermore, we find that the top managers of SMEs are a huge driver of CS. Oftentimes, they are even pioneers of good social and environmental practices. Finally, we identify four value dimensions (benevolence, achievement, power, and conformity values) according to the dimensions of the SVS that drive SMEs' top managers' engagement in CS. We contribute to the current state of research by conducting the first literature review that exclusively investigates how SMEs' executives influence the enterprise's commitment towards CS, based on the UET and the SVS. Thereby, we discuss implications and provide valuable recommendations for researchers, practitioners, and regulators alike.
Keywords: 350; adoption; corporate sustainability; diffusion theory; entrepreneurship; greenblushing; Schwartz Value System; small business; SMEs top manager; social responsibility; upper echelon theory